Different bacterial growth of major mastitis pathogens after coculturing with Staphylococcus chromogenes and Staphylococcus hominis in milk in vitro - Chuasakhonwilai, A.; Keeklangdon, P.; Chaisri, W.; Saipinta, D.; Photiboon, K.; Kaewmuangma, D.; Anuphom, W.; Intanon, M.; Suriyasathaporn, W. (Frontiers in Microbiology, 2025)
Non-aureus staphylococci (NAS) mainly cause subclinical bovine mastitis and often either spontaneously resolve or become persistent and challenging to treat. Additionally, coculturing with certain NAS strains may provide a protective effect against more severe pathogens, becoming the idea of a vaccine for treatment. Testing coinfection interactions directly in milk, the natural nutrient environment, is more appropriate than using standard culture media. Understanding these interactions may offer new insights into infection dynamics. Therefore, this study aimed to determine the pattern of bacterial growth in milk for the major mastitis pathogens, including S. uberis, S. agalactiae, and S. aureus, in single culture or coculture with certain S. chromogenes and S. hominis, which have been proven as NAS protective strains in vitro. For major mastitis pathogens, three mastitis strains of each pathogen were included. The stock major bacteria were prepared for 105 CFU/mL, while the stocked minor bacteria were adjusted to 109 CFU/mL. Cultures were incubated at 37 °C. After incubation for 0, 8, 12, and 24 h, all samples were collected to determine bacterial growth using selective media. Logarithm bacterial counts were used for statistical analysis using generalized mixed linear models. Results demonstrated distinct growth dynamics of major and minor mastitis pathogens in milk. For the first 12 h of incubation, marked increases were observed for major pathogens, but minor pathogens continued to increase slightly. S. aureus had the highest growth rate. The growth rate of S. uberis was higher when cocultured with S. chromogenes than in its single culture but S. agalactiae was higher when cocultured with both minor pathogens. No significant difference was found for the growth rate of S. aureus after coculture. Except for the higher growth of S. hominis cocultured with S. aureus, the growth of S. chromogenes in both single and coculture with most major pathogens was significantly higher than that of S. hominis. In conclusion, the in vitro proven protective NAS strains could survive in milk after coculture with major pathogens. This method can be applied as a tool to evaluate the interaction between mastitis pathogens and weakened pathogens of live-attenuated vaccines for treating mastitis.